The Effect of Training, Work Environment, Esprit de Corps, and Competence on Combat Readiness - Marsono Marsono; H.M. Kemalsyah (The Republic of Indonesia Defense University, 2025)
Personnel combat readiness is the main focus of the Indonesian Air Force units in carrying out their main tasks. Air Squadron 15 (Iswahjudi Air Force Base) is one of the Indonesian Air Force units that is expected to have maximum personnel combat readiness, but in reality, the combat readiness of personnel in this unit is not yet optimal. Personnel combat readiness can be influenced by various factors. This study used a quantitative method with a sample size of 59 people, and data analysis was carried out using path analysis techniques. The results of the study showed that training has a direct positive effect on combat readiness, the work environment had a direct positive effect on combat readiness, and environmental factors had a direct positive effect on combat readiness. Esprit de corps had a direct positive effect on combat readiness, and competence had a direct positive effect on combat readiness. Furthermore, training had a direct positive effect on competence, the work environment had a direct positive effect on competence, esprit de corps had a direct positive effect on competence, and training had a direct positive effect on esprit de corps. It is recommended that Air Squadron 15 improve the combat readiness of personnel by increasing and improving the training process, work environment, esprit de corps, and personnel competence. In addition, further research is needed on the combat readiness of personnel by considering other relevant aspects. It is recommended that the Indonesian Air Force leaders in air units increase the combat readiness of their personnel by adding/improving the variables that influence it.